2007
DOI: 10.1021/jp0660738
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Iron Phthalocyanine at the Initial Stage on Au(111) Surface

Abstract: Growth behavior of iron(II) phthalocyanine (FePc) molecules on Au(111) surface at the initial stage is studied with low-temperature scanning tunneling microscopy. The FePc molecules are separately adsorbed on the face-centered cubic and the hexagonal close-packed regions at the submonolayer regime, indicating that the molecular adsorption is greatly affected by the molecule−substrate interaction. At the monolayer regime, the molecules can form a close-packed ordered structure. When the FePc goes further to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
135
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 36 publications
29
135
2
Order By: Relevance
“…The ridge of the herringbone structure is perpendicular to one of these quasi-close-packed directions. For an MPc film, quasi-square lattices were commonly formed when the coverage was close to a monolayer, as clearly demonstrated for the molecules of CoPc [2,[13][14][15] and FePc [11,12].…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…The ridge of the herringbone structure is perpendicular to one of these quasi-close-packed directions. For an MPc film, quasi-square lattices were commonly formed when the coverage was close to a monolayer, as clearly demonstrated for the molecules of CoPc [2,[13][14][15] and FePc [11,12].…”
Section: Introductionmentioning
confidence: 69%
“…Chen et al reported the adsorption of FePc on the Au(111) surface in a low-coverage regime (< 0.1 ML), in which FePc molecules were found only in the fcc region [12,23]. They concluded that the adsorption of FePc is more stable on fcc than that on the hcp domain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations